(untitled) (Praxis Educativa, 2021)
August 19 marks the 100th anniversary of the birth of Juan Ricardo Nervi. TEACHER, pedagogue and teacher trainer. Someone who had the virtue to put his training - vocation of educator in dialogue with the most varied dimensions of culture, convinced of the strong humanistic sense of responsibility of those who educate.